Morphological binomials of various types in the Kharkiv Philological School founders’ works, the current state and prospects of the problem study - Olena Skorobogatova (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ., 2023)
The article is devoted to the study of morphological binomials in the scientific heritage of representatives of the Kharkiv Philological School (KhPhSch), in particular I. Sreznevskyi and O. Potebnia. The state of the development of the issue has been considered. Traditional and modern approaches to the characterization of morphological binomials, ways and methods of their study have been described.